Uptake, sequestration and tolerance of cadmium at cellular levels in the hyperaccumulator plant species Sedum alfredii - Tian, Shengke (Journal of experimental botany, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the Society for Experimental Biology.